2017
DOI: 10.17216/limnofish.323764
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Substrate Preference of Juvenile Mexican Dwarf Orange Crayfish (Cambarellus patzcuarensis) in Different Substrate Types

Abstract: Substrate is very important factor on growth and survival for crayfish in their entire life. Survival rate and growth of juveniles of the Mexican dwarf orange crayfish (Cambarellus patzcuarensis) were evaluated in aquaria with six different substrates covering their bottom. The six different substrates were plastic mesh, pebble, sand, basalt and calcite and bare glass without a cover as a control group.The study was carried out in two different experimental areas. In the first experiment, ten (mean body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There was biofilm present on TWC; however, it was physically inaccessible to the benthic C. cainii, providing no complementary food source. Accessible bottom substrates are very important in growth performance of crayfish (Karadal & Türkmen 2017). Substrates increase growth rates in shrimp and crayfish, by promoting the growth of periphyton for use as a complementary food source, or by providing habitat (Jones et al 2002;Schveitzer et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There was biofilm present on TWC; however, it was physically inaccessible to the benthic C. cainii, providing no complementary food source. Accessible bottom substrates are very important in growth performance of crayfish (Karadal & Türkmen 2017). Substrates increase growth rates in shrimp and crayfish, by promoting the growth of periphyton for use as a complementary food source, or by providing habitat (Jones et al 2002;Schveitzer et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[38]. Substrates used with different crayfish species Pacifactacus leniusculus [39] Cherax quadricarinatus [40], Cambarellus patzcuarensis [41], Procambarus clarkia [42] reported that substrates mimicking natural habitat situation had the best performance effect. In this study, fry in gravel substrate demonstrated the best growth response recording (1.77 ± 0.92 g), while control and sand recorded 1.57 ± 0.90 g and 1.45 ± 0.97 g respectively (Figure 2).…”
Section: Effect Of Different Substrates On Growth Of Labeo Victorianu...mentioning
confidence: 99%